Honeycomb structure and manufacturing method of honeycomb structure

By incorporating additives and using a slurry with clay minerals, the honeycomb structure achieves improved thermal shock resistance and heat-resistant impactability through uniform coat layer thickness and reduced gaps, addressing uneven thickness and stress concentration issues.

JP2025011571APending Publication Date: 2025-01-24NGK INSULATORS LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023113758
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing honeycomb structures with a coat layer containing magnetic particles face issues of uneven thickness and large gaps due to surface tension and firing contraction, leading to stress concentration and cracks, resulting in low heat-resistant impactability.

Method used

A honeycomb structure with a coat layer containing magnetic particles bound together, incorporating additives like Si, Al, and Mg, and using a slurry with clay minerals to ensure uniform thickness and reduce gaps, achieving a relative density of 75-95% and thickness of 20-100 μm, with a maximum gap width of 15 μm or less.

Benefits of technology

The solution enhances the honeycomb structure's thermal shock resistance and heat-resistant impactability by improving the uniformity and connectivity of the coat layer, preventing cracks and stress concentration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011571000001_ABST
    Figure 2025011571000001_ABST
Patent Text Reader

Abstract

To provide a honeycomb structure having high thermal shock resistance.SOLUTION: A honeycomb structure 1 includes: a substrate 2 being a cylindrical member with a plurality of cells 23 extending from one edge face to the other edge face; and a coat layer 3 disposed on a surface of an object cell 23a being at least part of the plurality of cells 23, in which magnetic substance particles bind to one another. The coat layer 3 includes at least one of elements Si, Al and Mg as an additive element. In the coat layer 3, a ratio of a sum of weight fractions of additive elements to a sum of weight fractions of major constituent elements of the magnetic substance particle is 1.7 wt% or more. Thus the honeycomb structure 1 having high thermal shock resistance can be achieved.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a honeycomb structure and a method for manufacturing a honeycomb structure. [Background technology]

[0002] Conventionally, a method called induction heating, which heats an object to be heated by electromagnetic induction, is known. Induction heating is performed by placing an induction heating coil near an object to be heated, which includes a magnetic material or a conductive material, and generating a magnetic field by the induction heating coil. For example, when a columnar object to be heated is heated, an induction heating coil is provided to surround the outer periphery of the object to be heated. The current to be passed through the induction heating coil when generating a magnetic field can be obtained, for example, by amplifying an alternating current from a high-frequency inverter with a transformer. Since induction heating can heat an object to be heated without contact, it is particularly useful when heating a material with low thermal conductivity or when heating an object under conditions where thermal contact is not easy. In addition, compared to indirect heating by thermal conduction, it is direct heating by self-heating, so it is also more energy efficient.

[0003] There is also known a technique for heating a catalyst carrier by induction heating. For example, in the catalyst carrier of Patent Document 1, metal particles are introduced into the internal space of selected cells in a ceramic substrate having a plurality of cells. The metal particles are fixed to the ceramic substrate while being fixed to each other by a fixing material. The metal particles generate heat in response to a change in the magnetic field. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-188272 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, when a coating layer containing magnetic particles is provided on the surface (inner peripheral surface) of the cells of the substrate, the thickness of the coating layer may become non-uniform. For example, when the cross-sectional shape of the cells is approximately square, the thickness of the coating layer at the corners of the cells becomes larger than that of other parts due to the influence of the surface tension of the slurry containing magnetic particles when the slurry is applied. In addition, a large gap occurs between the surface of the corners and the coating layer due to the influence of sintering shrinkage. In this case, when the thermal shock resistance is evaluated, stress concentration occurs at the boundary between the contact part between the coating layer and the cell surface and the non-contact part (the above-mentioned gap), and cracks occur in the substrate. In this way, the thermal shock resistance of the honeycomb structure provided with the coating layer is reduced.

[0006] The present invention has been made in consideration of the above problems, and has an object to provide a honeycomb structure having high thermal shock resistance. [Means for solving the problem]

[0007] The invention of aspect 1 is a honeycomb structure comprising a substrate which is a cylindrical member and has a plurality of cells extending from one end face to the other end face, and a coating layer which is provided on the surface of target cells which are at least a portion of the plurality of cells and in which magnetic particles are bonded to each other, the coating layer containing at least one of Si, Al and Mg as an additive element, and in the coating layer, the ratio of the sum of the weight fractions of the additive elements to the sum of the weight fractions of the main constituent elements of the magnetic particles is 1.7 wt% or more.

[0008] A second aspect of the present invention is the honeycomb structure of the first aspect, wherein the main constituent elements of the magnetic particles are Fe and Cr.

[0009] A third aspect of the present invention is the honeycomb structure of the first or second aspect, wherein in the coating layer, a compound containing the additional element is present on the surface of the magnetic particles.

[0010] A fourth aspect of the present invention relates to the honeycomb structure of any one of the first to third aspects, wherein the coating layer has a relative density of 75 to 95%.

[0011] A fifth aspect of the present invention is the honeycomb structure according to any one of the first to fourth aspects, wherein the coating layer has a thickness of 20 to 100 μm.

[0012] A sixth aspect of the present invention is the honeycomb structure according to any one of the first to fifth aspects, wherein the maximum width of the gap between the surface of the target cell and the coating layer is 15 μm or less.

[0013] The invention of embodiment 7 is a honeycomb structure of any one of embodiments 1 to 6, wherein the coating layer has a thick-walled portion where the thickness is locally maximum and a thin-walled portion where the thickness is locally minimum, and the ratio of the thickness of the thick-walled portion to the thickness of the thin-walled portion is 2 or less.

[0014] The invention of embodiment 8 is a method for manufacturing a honeycomb structure, comprising the steps of: a) preparing a substrate which is a cylindrical member and has a plurality of cells extending from one end face to the other end face; b) preparing a slurry containing magnetic particles and a clay mineral; c) applying the slurry to surfaces of target cells which are at least a portion of the plurality of cells; and d) drying and firing the slurry applied to the target cells to form a coating layer on the surfaces of the target cells.

[0015] A ninth aspect of the present invention relates to the method for manufacturing a honeycomb structure according to the eighth aspect, wherein the clay mineral includes at least one selected from the group consisting of montmorillonite, sepiolite, hectorite, halloysite, and attapulgite. Effect of the Invention

[0016] According to the present invention, it is possible to provide a honeycomb structure having high thermal shock resistance. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a cross-sectional view showing a configuration of an induction heating device. [Diagram 2] FIG. 2 is a plan view showing a honeycomb structure. [Diagram 3] FIG. 2 is a cross-sectional view showing a target cell and its vicinity. [Figure 4] FIG. 4 is a cross-sectional view showing a coating layer at a corner portion. [Diagram 5] FIG. 4 is a cross-sectional view showing a coating layer on a flat portion. [Figure 6] FIG. 4 is a cross-sectional view showing a coating layer at a corner portion. [Figure 7] FIG. 4 is a cross-sectional view showing a coating layer at a corner portion. [Figure 8] 1A to 1C are diagrams illustrating a manufacturing flow of a honeycomb structure. [Figure 9] FIG. 13 is a diagram showing a state in which a slurry is applied to a target cell. [Figure 10A] 1 is an SEM image showing a target cell having a coating layer thickness of less than 20 μm. [Figure 10B] 1 is an SEM image showing a target cell having a coating layer thickness of 20 μm or more. [Figure 11A] 1 is an SEM image showing a target cell with a thick to thin thickness ratio greater than 2:1. [Figure 11B] 1 is an SEM image showing a target cell in which the ratio of the thickness of the thick portion to the thickness of the thin portion is less than or equal to 2. [Figure 12] FIG. 2 is a diagram showing an induction heating coil. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] FIG. 1 is a cross-sectional view showing a configuration of an induction heating device 4. The induction heating device 4 is provided in a flow path 9 of exhaust gas discharged from an engine of an automobile or the like. The induction heating device 4 includes an exhaust gas purification section 41, a coil section 42, and a fixing member 43. The exhaust gas purification section 41 includes a honeycomb structure 1 which is a catalyst carrier, and a catalyst supported on the honeycomb structure 1. The honeycomb structure 1 is a cylindrical member, and has a plurality of cells 23 (see FIG. 2 described later) extending along the flow path 9. Exhaust gas flows through the plurality of cells 23. The catalyst in the exhaust gas purification section 41 may be, for example, a precious metal catalyst, or may be a catalyst that does not use a precious metal. Details of the honeycomb structure 1 will be described later.

[0019] The coil portion 42 is a conductive wire formed in a spiral shape, and surrounds the honeycomb structure 1. The fixing member 43 fixes the exhaust gas purification portion 41 and the coil portion 42 within the flow path 9. The coil portion 42 is connected to an AC power source (not shown), and a periodically changing magnetic field is generated around the coil portion 42 when an AC current flows through the coil portion 42. As described later, the honeycomb structure 1 contains magnetic particles inside, and the temperature of the honeycomb structure 1 rises in response to changes in the magnetic field. As the temperature of the honeycomb structure 1 rises, the temperature of the catalyst also rises, promoting the catalytic reaction.

[0020] Fig. 2 is a simplified plan view of the honeycomb structure 1. As described above, the honeycomb structure 1 is a tubular member that is long in one direction, and Fig. 2 shows one end face in the longitudinal direction (the left-right direction in Fig. 1, and the direction perpendicular to the paper surface of Fig. 2) of the honeycomb structure 1. The honeycomb structure 1 in the following description is in a state in which no catalyst is yet supported thereon.

[0021] The honeycomb structure 1 includes a base material 2 and a coating layer 3. The base material 2 is a cylindrical member formed of a porous sintered body, and has two end faces 29 (see FIG. 1) in the longitudinal direction. The base material 2 includes a cylindrical outer wall 21 and partition walls 22. The cylindrical outer wall 21 is a cylindrical portion extending in the longitudinal direction. The cross-sectional shape of the cylindrical outer wall 21 perpendicular to the longitudinal direction is, for example, substantially circular. The cross-sectional shape may be another shape, such as a polygon.

[0022] The partition wall 22 is a lattice-like portion provided inside the cylindrical outer wall 21 and divides the inside into a plurality of cells 23. Each of the plurality of cells 23 is a space extending in the longitudinal direction. Each cell 23 extends from one end face 29 to the other end face 29. The catalyst described above is introduced into the cell 23. The cross-sectional shape of each cell 23 perpendicular to the longitudinal direction is, for example, approximately square. The cross-sectional shape may be other shapes such as polygonal or circular. The plurality of cells 23 have the same cross-sectional shape in principle. The plurality of cells 23 may include cells 23 with different cross-sectional shapes. The substrate 2 is a cell structure in which the inside is divided into a plurality of cells 23 by the partition walls 22.

[0023] The cylindrical outer wall 21 and the partition wall 22 are each a porous portion. The cylindrical outer wall 21 and the partition wall 22 are formed of, for example, ceramics such as cordierite. The material of the cylindrical outer wall 21 and the partition wall 22 may be ceramics other than cordierite, or may be a material other than ceramics. Typically, the material has insulating properties.

[0024] The porosity of the substrate 2 including the cylindrical outer wall 21 and the partition walls 22 is, for example, 20% or more, and preferably 30% or more. The porosity of the substrate 2 is, for example, 80% or less, and preferably 70% or less. The open porosity of the substrate 2 is, for example, 40% or more, and preferably 55% or more. The open porosity of the substrate 2 is, for example, 65% or less. The porosity and open porosity of the substrate 2 can be measured by Archimedes' method.

[0025] The average pore diameter of the substrate 2 is, for example, 5 μm or more, and preferably 8 μm or more. The average pore diameter of the substrate 2 is, for example, 30 μm or less, and preferably 25 μm or less. The average pore diameter can be measured by a mercury porosimeter. The surface opening ratio of the substrate 2 is, for example, 20% or more, and preferably 25% or more. The surface opening ratio of the substrate 2 is, for example, 60% or less, and preferably 50% or less. The surface opening ratio is the ratio of the area of ​​the region where the pores are open to the surface of the substrate 2, and can be obtained by image analysis of an SEM (scanning electron microscope) image of the surface. The SEM image is taken at, for example, 500 times magnification.

[0026] The cell density of the substrate 2 (i.e., the number of cells 23 per unit area in a cross section perpendicular to the longitudinal direction) is, for example, 10 cells / cm 2 More than 20 cells / cm, preferably 20 cells / cm 2 More preferably, 30 cells / cm 2 That is all. The cell density is, for example, 200 cells / cm 2 ≤ 150 cells / cm 2 2, the size of the cells 23 is drawn larger than in reality, and the number of the cells 23 is drawn smaller than in reality. The size and number of the cells 23 may be variously changed.

[0027] The coating layer 3 is a porous sintered body, and is provided on some of the cells 23a (hereinafter referred to as "target cells 23a"). The coating layer 3 extends over the entire circumference of the target cells 23a, and typically covers almost the entire surface (i.e., the inner peripheral surface) of the target cells 23a. The target cells 23a on which the coating layer 3 is provided are preferably arranged in an evenly distributed manner. In the example of FIG. 2, at least one cell 23 on which the coating layer 3 is not provided exists between each target cell 23a and another target cell 23a. This allows the honeycomb structure 1 to be heated more rapidly and the temperature to be reached to be higher than when the coating layer 3 is formed on all the cells 23. In fact, it has been confirmed that in a honeycomb structure having 300 cells, when coating layers are formed only on 9, 21, 45, and 61 cells that are positioned at approximately equal intervals so as not to be adjacent to each other, the temperature can be raised more rapidly and the temperature to be reached is higher than when coating layers are formed on all the cells. Depending on the design of the honeycomb structure 1, all the cells 23 may be target cells 23a.

[0028] FIG. 3 is a cross-sectional view showing one target cell 23a and its vicinity, and shows a cross section perpendicular to the longitudinal direction. In this specification, a "cross section" refers to a cross section perpendicular to the longitudinal direction of the honeycomb structure 1, unless otherwise specified. In the example of FIG. 3, the cross-sectional shape of each cell 23, 23a perpendicular to the longitudinal direction is substantially square. The inner peripheral surface of each cell 23, 23a has four corners 231 and four flat portions 232. In each cell 23, 23a, two adjacent corners 231 are connected by the flat portion 232. Each corner 231 is formed by an intersection of the lattice-shaped partition walls 22, and the flat portion 232 is formed by a portion (also called a rib) between the intersections of the partition walls 22.

[0029] Fig. 4 is a cross-sectional view showing the coating layer 3 at the corner portion 231, and Fig. 5 is a cross-sectional view showing the coating layer 3 at the flat portion 232. The coating layer 3 is a layer formed by bonding magnetic particles 31 to each other by sintering. In Figs. 4 and 5, the magnetic particles 31 are shown typically as circles. The magnetic particles 31 may be in the form of fine particles, and small pieces of magnetic material can also be regarded as magnetic particles.

[0030] The magnetic particles 31 are, for example, metal particles. The preferred magnetic particles 31 are made of ferritic stainless steel and contain Fe (iron) and Cr (chromium) as main constituent elements. Here, the main constituent elements are elements that account for 3 wt% or more of the constituent elements of the magnetic particles 31. The magnetic particles 31 may be made of other materials that can be induction heated. For example, martensitic stainless steel, austenitic stainless steel, Invar, and Super Invar can be used. The magnetic particles 31 may be other than metal particles.

[0031] The coating layer 3 contains at least one of Si, Al, and Mg as an additive element. The additive element is an element that is not included in the main constituent elements of the magnetic grains 31. In principle, the additive element is an element that is not included in the magnetic grains 31, but may be unavoidably included in the magnetic grains 31 as an impurity or the like. As described below, in forming the coating layer 3, a raw material containing the additive element is used together with the magnetic grains 31. As a result, in the coating layer 3, the ratio of the sum of the weight fractions of the additive elements to the sum of the weight fractions of the main constituent elements of the magnetic grains 31 (hereinafter referred to as the "ratio of the additive elements to the magnetic grains") is 1.7 wt% or more. The weight fraction of each element is the ratio of the weight of the element to the weight of the coating layer 3.

[0032] For example, when the magnetic particles 31 are ferritic stainless steel particles and the raw material containing the additive element is montmorillonite, the main constituent elements of the magnetic particles 31 are Fe and Cr, and the additive elements include all of Si, Al, and Mg. In this case, the ratio of the additive element to the magnetic particles is the ratio of the sum of the weight fractions of Si, Al, and Mg to the sum of the weight fractions of Fe and Cr. For example, when the coating layer 3 does not contain Mg, the additive elements are only Si and Al, and when the coating layer 3 does not contain Al, the additive elements are only Si and Mg.

[0033] As described later, in the honeycomb structure 1 in which the ratio of the additive element to the magnetic particles in the coating layer 3 is 1.7 wt % or more, the thermal shock resistance is improved. When obtaining the ratio of the additive element to the magnetic particles, a cross section of the coating layer 3 is measured using an EDS (energy dispersive X-ray analyzer) to obtain the weight fraction of each main constituent element of the magnetic particles 31 and the weight fraction of each additive element. Then, the sum of the weight fractions of the additive elements is divided by the sum of the weight fractions of the main constituent elements of the magnetic particles 31 to obtain the ratio of the additive element to the magnetic particles.

[0034] Typically, a compound containing an additive element is present on the surface of the magnetic grain 31. The surface of the magnetic grain 31 includes not only the surface of the magnetic grain 31 forming the outer edge of the coating layer 3, but also the interface between the magnetic grain 31 and the pores formed inside the coating layer 3. The compound does not contain, for example, a main constituent element of the magnetic grain 31. The compound may contain any of the main constituent elements of the magnetic grain 31. For example, by performing element mapping on the cross section of the coating layer 3 using EDS, it is possible to confirm whether or not a compound containing an additive element is present on the surface of the magnetic grain 31. The additive element may be present at the interface between the magnetic grains 31, or may be dissolved in the crystal phase of the magnetic grain 31.

[0035] The relative density of the coat layer 3 is, for example, 75% or more, preferably 80% or more. This ensures the connectivity of the magnetic particles 31, and makes it possible to increase the temperature that the honeycomb structure 1 reaches by induction heating. If the relative density of the coat layer 3 is excessively high, the amount of thermal expansion of the coat layer 3 increases, which may affect the thermal shock resistance of the honeycomb structure 1. The relative density of the coat layer 3 is, for example, 95% or less, preferably 90% or less. When acquiring the relative density of the coat layer 3, an SEM image (magnification: 500 times) showing a cross section of the coat layer 3 at the corner portion 231 is acquired, and a calculation range (a range surrounded by a line marked with a symbol A1 in FIG. 4) including only the coat layer 3 is set. Next, in the SEM image, the calculation range A1 is binarized using a threshold value that allows the white area showing the magnetic particles 31 to be distinguished from other areas, and the area ratio of the white area is acquired as the relative density of the coat layer 3.

[0036] In forming the coating layer 3 described later, a slurry is applied to the surface (inner peripheral surface) of the target cell 23a. When the cross-sectional shape of the target cell 23a is substantially square, as shown in FIG. 3, the surface tension of the slurry causes the thickness of the coating layer 3 to be locally minimum at the center between two adjacent corners 231 (the center of the flat surface portion 232), and the portion of the coating layer 3 located at the center becomes a thin portion 37. Furthermore, at the corners 231, the thickness of the coating layer 3 becomes locally maximum, and the portion of the coating layer 3 located at the corners 231 becomes a thick portion 36. In the following description, when the term "thickness of the coating layer 3" is simply used, it means the thickness of the thin portion 37 at the flat surface portion 232.

[0037] The thickness of the coating layer 3 (i.e., the thickness of the thin portion 37) is, for example, 20 μm or more, and preferably 30 μm or more. This makes it possible to increase the temperature reached by the honeycomb structure 1 by induction heating. If the thickness of the coating layer 3 is excessively large, the cost of forming the coating layer 3 increases. The thickness of the coating layer 3 is, for example, 100 μm or less, and preferably 80 μm or less. When measuring the thickness of the thin portion 37, an SEM image (500 times magnification) showing a cross section of the coating layer 3 is obtained at the center between two adjacent corners 231 (the center of the flat portion 232). Then, parallel lines L1 and L2 are set along both sides of the coating layer 3 in the SEM image (see FIG. 5), and the distance D1 between the parallel lines L1 and L2 is measured as the thickness of the thin portion 37. When abnormal concave or convex portions are present on the surface of the coating layer 3 shown in the SEM image, the parallel lines L1 and L2 are set along the surface with the concave or convex portions removed.

[0038] In addition, it is preferable that the thickness of the thick portion 36 is not excessively larger than the thickness of the thin portion 37. The ratio of the thickness of the thick portion 36 to the thickness of the thin portion 37 is preferably 2 times or less, and more preferably 1.8 times or less. In this way, in the honeycomb structure 1 in which the uniformity of the thickness of the coating layer 3 is improved, it is possible to suppress the decrease in thermal shock resistance caused by the non-uniformity of the thickness. When measuring the thickness of the thick portion 36, as shown in FIG. 6, an SEM image (500 times magnification) showing the cross section of the coating layer 3 at the corner portion 231 is obtained. Next, a tangent line L3 is set in the SEM image at an inclination angle of 45° with respect to the flat portion 232 and in contact with the outer periphery of the thick portion 36, and the shortest distance D3 between the tangent line L3 and the inner periphery of the thick portion 36 is measured as the thickness of the thick portion 36.

[0039] When the cross-sectional shape of the target cell 23a is a regular polygon other than a square, typically, the portions of the coating layer 3 facing the corners are thick portions, and the central portion between two adjacent thick portions is thin portion. Even when the cross-sectional shape of the target cell 23a is circular, depending on the method of forming the coating layer 3, thick portions whose thickness is locally maximum (for example, in each range obtained by dividing the circumference into four equal parts) and thin portions whose thickness is locally minimum are generated. In either case, by making the ratio of the thickness of the thick portions to the thickness of the thin portions equal to or less than two, the thermal shock resistance can be improved more reliably.

[0040] As described above, since the coat layer 3 is a sintered body, a gap 239 (hereinafter referred to as a "corner gap 239") may occur between the surface of the corner 231 of the target cell 23a and the coat layer 3 due to firing shrinkage. The width of the corner gap 239 is, for example, 15 μm or less, and preferably 12 μm or less. In the thermal shock resistance evaluation described later, stress concentration occurs at the boundary between the contact portion between the coat layer 3 and the cell surface and the non-contact portion (the corner gap 239). Therefore, in a honeycomb structure 1 having a small width of the corner gap 239, the thermal shock resistance can be more reliably improved. The width of the corner gap 239 may be 0. A gap may occur between the surface of the target cell 23a and the coat layer 3 at a position other than the corner 231, but when the cross-sectional shape of the target cell 23a is approximately square, the width of the corner gap 239 is the maximum width of the gap between the surface of the target cell 23a and the coat layer 3.

[0041] When measuring the width of the corner gap 239, as shown in Fig. 7, an SEM image (500x) showing a cross section of the coating layer 3 at the corner 231 is obtained. Next, a tangent L4 is set in the SEM image at an inclination angle of 45° with respect to the flat portion 232 and in contact with the corner 231 (the inner peripheral surface of the target cell 23a), and the shortest distance D4 between the tangent L4 and the outer periphery of the thick portion 36 is measured as the width of the corner gap 239. Even when the cross-sectional shape of the target cell 23a is other than a substantially square shape (polygonal, circular, etc.), the thermal shock resistance of the honeycomb structure 1 in which the maximum width of the gap between the surface of the target cell 23a and the coating layer 3 is 15 µm or less can be more reliably improved.

[0042] Next, an example of the manufacturing method of the honeycomb structure 1 will be described. FIG. 8 is a diagram showing the flow of manufacturing the honeycomb structure 1. In the manufacturing of the honeycomb structure 1, first, the base material 2 is prepared (step S11). In the base material 2, a plurality of cells 23 extending from one end face 29 to the other end face 29 are provided (see FIGS. 1 and 2). Various known methods may be used to manufacture the base material 2. Typically, the base material 2 is manufactured by extrusion molding of a clay, drying and firing.

[0043] Next, a slurry for forming the coating layer is prepared (step S12). In preparing the slurry, magnetic particles, which are a powder of a magnetic body, a clay mineral powder, and a dispersion medium (here, water) are weighed and mixed in a container. As the magnetic particles, powders of the materials described above can be used. The clay mineral is a layered mineral, and preferably includes at least one selected from the group consisting of montmorillonite, sepiolite, hectorite, halloysite, and attapulgite. A slurry containing a clay mineral has a higher shear strength (shear strength) and viscosity than a slurry not containing a clay mineral.

[0044] The amount of clay mineral added to the magnetic particles is preferably 4 vol% or more. This makes it possible to reduce the width of the corner gap 239 described above in the formed coating layer 3 and to reduce the ratio of the thickness of the thick portion 36 to the thickness of the thin portion 37. The amount of clay mineral added to the magnetic particles is preferably 9 vol% or less, which prevents the viscosity of the slurry from becoming excessively high. The aforementioned additive elements contained in the coating layer 3 are, in principle, elements derived from the clay minerals. In this embodiment, among the raw materials contained in the slurry, raw materials other than the clay minerals contain almost no additive elements.

[0045] When the slurry is prepared, the slurry is applied to the surface of the target cell 23a of the substrate 2 (step S13). When applying the slurry, the substrate 2 is upright so that the multiple cells 23 face up and down, and as shown in FIG. 9, an upper jig 81 and a lower jig 82 are attached to the upper and lower parts of the substrate 2, respectively. In detail, the upper jig 81 is a substantially cylindrical member and has an inner diameter slightly larger than the diameter of the substrate 2. A ring-shaped groove is provided in the lower part of the inner peripheral surface of the upper jig 81, and a ring-shaped rubber tube 811 is disposed in the groove. The upper jig 81 is fitted into the upper part of the substrate 2 and contacts the outer peripheral surface of the substrate 2 via the rubber tube 811. The lower jig 82 is a substantially annular member and has an inner diameter slightly smaller than the diameter of the substrate 2. A silicon O-ring 821 is provided in a portion of the upper surface of the lower jig 82 near the inner circumference. The substrate 2 is placed on the lower jig 82, and the outer periphery of the lower end face 29 of the substrate 2 is in contact with the lower jig 82 via a silicon O-ring 821.

[0046] When the upper jig 81 and the lower jig 82 are attached to the substrate 2, a predetermined amount of slurry is poured into the upper jig 81, and the upper end surface 29 of the substrate 2 is filled with the slurry. At this time, a covering material (not shown) that covers the upper end surface 29 is provided on the substrate 2, and a hole is formed in the covering material in a portion facing the target cell 23a. Therefore, the slurry can flow only into the target cell 23a. Next, the space on the lower end surface 29 side of the substrate 2 is vacuum-suctioned by a pump. As a result, the slurry flows into the target cell 23a from the opening on the upper end surface 29 side of the target cell 23a, and the slurry is applied to the surface (inner peripheral surface) of the target cell 23a. The slurry that has passed through the target cell 23a flows out from the opening on the lower end surface 29 side to the outside. When the application of the slurry to the target cell 23a is completed, the upper jig 81 and the lower jig 82 are removed from the substrate 2.

[0047] Next, the slurry applied to the target cells 23a is dried. As described above, the slurry containing clay minerals has high shear strength, so that the slurry is prevented from coagulating at the corners 231 due to surface tension. That is, the uniformity of the thickness of the slurry after drying (uniformity in the circumferential direction of the target cells 23a) is increased. The application and drying of the slurry may be repeated multiple times. Then, firing (heat treatment) is performed in a vacuum atmosphere. The firing temperature is, for example, 1050 to 1250°C. The firing time is, for example, 5 to 70 minutes. As a result, the coating layer 3 is formed on the surface of the target cells 23a, and the honeycomb structure 1 is manufactured (step S14). The above firing temperature and firing time are merely examples and may be changed as appropriate. It is considered that the clay minerals contained in the slurry are decomposed by firing, and the clay minerals are hardly present in the honeycomb structure 1 as they are.

[0048] Next, with reference to Table 1, Examples 1 to 9 of the honeycomb structure according to the present invention and Comparative Examples 1 and 2 will be described.

[0049] [Table 1]

[0050] <Production of honeycomb structure> (Examples 1 to 9) The magnetic particles, stainless steel (SUS430) powder, clay mineral montmorillonite, and ion-exchanged water were weighed. In Table 1, the amount [vol%] of montmorillonite relative to the stainless steel powder in each of Examples 1 to 9 is shown in the "Amount of Montmorillonite Added" column, and the amount [parts by weight] of water relative to the stainless steel powder and montmorillonite is shown in the "Water Ratio" column. These were placed in a container together with ZrO2 balls (φ5 mm) and mixed using a rotation-revolution type mixer to prepare a slurry. Next, a base material was prepared whose inside was divided into a plurality of cells by partition walls. As described with reference to FIG. 9, an upper jig and a lower jig were attached to the upper and lower parts of the base material, respectively, and the slurry was applied to the surface of each cell. The slurry was then dried. In Table 1, the number of times the slurry was applied and dried is shown in the "Number of Coats" column. Then, firing was performed in a vacuum atmosphere. In Table 1, the firing temperature and firing time are shown in the "Firing Schedule" column. The temperature rise rate was 500° C. / hr. Through the above treatment, the honeycomb structures of Examples 1 to 9 were obtained.

[0051] (Comparative Examples 1 to 2) Stainless steel (SUS430) powder, water-soluble binder, thickener, and ion-exchanged water were weighed. In Comparative Examples 1 and 2, montmorillonite was not added to the slurry. These were placed in a container together with ZrO2 balls (φ5 mm) and mixed using a rotation-revolution type mixer to prepare a slurry. The slurry was applied and dried in the same manner as in Examples 1 to 9. Thereafter, the substrate was held at 180°C for 4 hours in an air atmosphere, and then held at 450°C for 6 hours to perform degreasing. After degreasing, firing was performed in the same manner as in Examples 1 to 9 to obtain honeycomb structures of Comparative Examples 1 and 2.

[0052] <Coat layer measurement> For the honeycomb structures of Examples 1 to 9 and Comparative Examples 1 to 2, the ratio of the additive element to the magnetic particle, the thickness of the coating layer, the relative density of the coating layer, the width of the corner gap, and the ratio of the thickness of the thick part to the thin part were measured. In obtaining the ratio of the additive element to the magnetic particle, the mirror-polished cross section of the coating layer was measured using EDS and a DX200s Digital Pulse Processor manufactured by RaySpec, and the weight fraction of each main constituent element of the magnetic particle and the weight fraction of each additive element were obtained. Then, the sum of the weight fractions of the additive elements was divided by the sum of the weight fractions of the main constituent elements of the magnetic particle to obtain the ratio of the additive element to the magnetic particle. Here, the main constituent elements of the magnetic particle are Fe and Cr, and the additive elements are Si, Al, and Mg, so in Table 1, the ratio of the additive element to the magnetic particle is written as "(Si+Al+Mg) / (Fe+Cr)".

[0053] In Comparative Examples 1 and 2, the slurries did not contain montmorillonite, but at least one element of Si, Al, and Mg was inevitably contained as an impurity, etc., so that (Si+Al+Mg) / (Fe+Cr) was greater than 0 wt% and less than 1.7 wt%. On the other hand, in Examples 1 to 9, in which the slurries contained montmorillonite, (Si+Al+Mg) / (Fe+Cr) was 1.7 wt% or more in all cases.

[0054] In the measurement of the thickness of the coating layer, the relative density of the coating layer, the width of the corner gap, and the ratio of the thickness of the thick part to the thin part, an SEM image (magnification 500 times) was obtained using an SEM (JSM-IT500 manufactured by JEOL Corporation), and the image analysis was performed using the image analysis software "Image-pro Premier 9.3" manufactured by Media Cybernetics. As described with reference to FIG. 5, the distance between parallel lines along both sides of the thin part in the SEM image showing the thin part was measured as the thickness of the coating layer. FIG. 10A shows an SEM image of a target cell having a coating layer thickness of less than 20 μm, and FIG. 10B shows an SEM image of a target cell having a coating layer thickness of 20 μm or more. As described with reference to FIG. 4, a calculation range including only the coating layer was set in the SEM image showing the thick part, the calculation range was binarized with a threshold value that can distinguish between magnetic particles and other areas, and the area ratio of the area showing the magnetic particles was obtained as the relative density of the coating layer.

[0055] As described with reference to FIG. 7, in the SEM image showing the thick portion, a tangent line was set at an inclination angle of 45° with respect to the flat portion and tangent to the corner, and the shortest distance between the tangent line and the outer periphery of the thick portion was measured as the width of the corner gap. As described with reference to FIG. 6, in the SEM image showing the thick portion, a tangent line was set at an inclination angle of 45° with respect to the flat portion and tangent to the outer periphery of the thick portion, and the shortest distance between the tangent line and the inner periphery of the thick portion was measured as the thickness of the thick portion. Then, the thickness of the thick portion was divided by the thickness of the coating layer (thickness of the thin portion) described above to obtain the ratio of the thickness of the thick portion to the thin portion. FIG. 11A shows an SEM image of a target cell in which the width of the corner gap is greater than 15 μm and the ratio of the thickness of the thick portion to the thin portion is greater than 2 times, and FIG. 11B shows an SEM image of a target cell in which the width of the corner gap is 15 μm or less and the ratio of the thickness of the thick portion to the thin portion is 2 times or less.

[0056] <Induction heating characteristic evaluation> As shown in Fig. 12, a honeycomb structure 1 was placed inside an induction heating coil 71. The induction heating coil 71 was driven for 180 seconds under conditions of a frequency of 100 kHz and a power of 0.5 kW, and the reached temperature was measured by a thermocouple 72 provided inside the honeycomb structure 1. As shown in Table 1, the honeycomb structures of Examples 1 to 5, 7 to 9 and Comparative Examples 1 and 2 all reached temperatures of 390°C or higher. On the other hand, the honeycomb structure of Example 6, in which the thickness of the coating layer was less than 20 µm, reached a temperature of 210°C.

[0057] <Thermal shock resistance evaluation> The evaluation was performed by moving the bottom of the hearth lifting furnace, on which the honeycomb structure was placed, up and down, using a hearth lifting furnace maintained at 700°C. Specifically, the hearth was positioned at the rising end, and the honeycomb structure was maintained in the furnace for 10 minutes. Thereafter, the hearth was positioned at the falling end, and the honeycomb structure was placed outside the furnace (room temperature atmosphere), and was exposed to air from a blower for 5 minutes. The above-mentioned cooling and heating cycle was performed 100 times, and then the appearance of the honeycomb structure was observed. In Table 1, the evaluation result was marked as × when cracks were confirmed in the honeycomb structure, and the evaluation result was marked as ○ when no cracks were confirmed. The evaluation results of the thermal shock resistance of the honeycomb structures of Examples 1 to 9 were ○, while the evaluation results of the thermal shock resistance of the honeycomb structures of Comparative Examples 1 and 2 were ×. It can be said that the honeycomb structures with the evaluation results of the thermal shock resistance of ○ also have durability against repeated thermal shock.

[0058] <Considerations about the coating layer> In the honeycomb structures of Comparative Examples 1 and 2, in which the slurry does not contain clay minerals, the slurry is likely to aggregate at the corners due to surface tension immediately after application of the slurry, so that the thickness of the slurry becomes excessively thick at the corners and excessively thin at the flat surfaces. When the slurry is fired, large voids are generated between the corner surfaces of the target cells and the coating layer due to firing shrinkage. As a result, in the thermal shock resistance evaluation, it is considered that stress concentration occurs at the boundary between the contact portion between the coating layer and the cell surface and the non-contact portion (the above-mentioned void), and cracks are likely to occur in the base material.

[0059] In contrast, in Examples 1 to 9, the slurry becomes a Bingham fluid by adding montmorillonite, which is a clay mineral, to the slurry, and shear stress is applied in a stationary state. That is, the slurry does not flow until the shear stress exceeds the yield value, and the aggregation of the slurry at the corners due to surface tension is suppressed immediately after the application of the slurry. In addition, it has been found that the relative density of the magnetic particles after drying and before firing is increased by adding montmorillonite to the slurry, and the amount of firing shrinkage is reduced. Furthermore, it has been confirmed that montmorillonite decomposes and generates gas during firing, and the generation of the gas makes it easier for closed pores to be generated in the coating layer, suppressing excessive densification of the magnetic particles. In this respect, the amount of firing shrinkage is also reduced. As a result, compared to Comparative Examples 1 and 2, it is considered that the adhesion of the coating layer at the corners is improved and the gap between the corners and the coating layer is reduced, suppressing the occurrence of cracks due to stress concentration in the thermal shock resistance evaluation.

[0060] In the honeycomb structure of Example 6, the thickness of the coating layer was small (less than 20 μm), so the temperature reached in the induction heating characteristic evaluation was significantly low. Therefore, it can be said that in order to increase the temperature reached, it is preferable that the thickness of the coating layer is 20 μm or more. In the honeycomb structure of Example 7, the thickness of the coating layer is 50 μm, but the temperature reached was relatively low, less than 400° C. This is thought to be because in Example 7, the relative density of the coating layer is small (less than 75%), so the connectivity between the magnetic particles is low and eddy currents are difficult to flow. In other words, in order to increase the temperature reached, it can be said that it is preferable to set the relative density of the coating layer to 75% or more and increase the filling rate of the magnetic particles.

[0061] As described above, the honeycomb structure 1 is a cylindrical member, and includes the substrate 2 having a plurality of cells 23 extending from one end face 29 to the other end face 29, and the coating layer 3 provided on the surface of target cells 23a, which are at least a part of the plurality of cells 23, and in which magnetic particles 31 are bonded to each other. The coating layer 3 contains at least one element of Si, Al, and Mg as an additive element. In the coating layer 3, the ratio of the sum of the weight fractions of the additive elements to the sum of the weight fractions of the main constituent elements of the magnetic particles 31 is 1.7 wt% or more. This makes it possible to provide a honeycomb structure 1 having high thermal shock resistance (including durability against repeated thermal shock).

[0062] Preferably, the maximum width of the gap between the surface of the target cell 23a and the coating layer 3 is 15 μm or less, and / or the ratio of the thickness of the thick portion 36 to the thickness of the thin portion 37 in the target cell 23a is 2 or less. This makes it possible to more reliably improve the thermal shock resistance of the honeycomb structure 1.

[0063] Preferably, the relative density of the coating layer 3 is 75 to 95% and / or the thickness of the coating layer 3 is 20 to 100 μm, which allows the honeycomb structure 1 to reach a high temperature during induction heating.

[0064] Preferably, the main constituent elements of the magnetic particles 31 are Fe and Cr. Such magnetic particles 31 have a good balance between electrical resistivity and magnetic permeability, and improve heating efficiency. Furthermore, since the magnetic particles 31 contain Cr, a coating layer 3 with excellent corrosion resistance can be obtained.

[0065] Preferably, in the coating layer 3, a compound containing an additive element is present on the surface of the magnetic particles 31. This allows the compound to inhibit sintering of the magnetic particles 31 to some extent, and makes it possible to control the structure of the coating layer 3 containing the magnetic particles 31 (i.e., the connectivity of the magnetic particles 31, the outer shape and relative density of the coating layer 3, etc.).

[0066] The manufacturing method of the honeycomb structure 1 includes a step of preparing a base material 2 having a plurality of cells 23 provided therein (step S11), a step of preparing a slurry containing magnetic particles and a clay mineral (step S12), a step of applying the slurry to surfaces of target cells 23a which are at least a part of the plurality of cells 23 (step S13), and a step of forming a coating layer 3 on the surfaces of the target cells 23a by drying and firing the slurry applied to the target cells 23a (step S14). This makes it possible to provide a honeycomb structure 1 having high thermal shock resistance.

[0067] Preferably, the clay mineral includes at least one selected from the group consisting of montmorillonite, sepiolite, hectorite, halloysite and attapulgite, whereby the thermal shock resistance of the honeycomb structure 1 can be improved more reliably.

[0068] The above honeycomb structure 1 and the manufacturing method of the honeycomb structure 1 can be modified in various ways.

[0069] As long as high thermal shock resistance is realized in the honeycomb structure 1, the relative density of the coating layer 3 may be outside the range of 75 to 95%, and the thickness of the coating layer 3 may be outside the range of 20 to 100 μm. In addition, the maximum width of the gap between the surface of the target cell 23a and the coating layer 3 may be greater than 15 μm, and the thickness of the thick portion 36 may be greater than twice the thickness of the thin portion 37.

[0070] The honeycomb structure 1 may be manufactured by a method other than the manufacturing method shown in Fig. 8. The honeycomb structure 1 may be used for purposes other than as a catalyst carrier.

[0071] The configurations in the above-described embodiment and each of the modified examples may be combined as appropriate as long as they are not mutually inconsistent. [Explanation of symbols]

[0072] 1. Honeycomb structure 2 Base material 3 Coating Layer 23 Cell 23a Target cell 29 End face (of substrate) 31 Magnetic particles 36 Thick wall part 37 Thin Section 239 Corner void S11~S14 steps

Claims

1. A honeycomb structure, A substrate that is a cylindrical member and has a plurality of cells extending from one end surface to the other end surface; a coating layer provided on a surface of a target cell which is at least a part of the plurality of cells, the coating layer being made of magnetic particles bonded to each other; Equipped with the coating layer contains at least one element selected from the group consisting of Si, Al, and Mg as an additive element; A honeycomb structure, wherein in the coating layer, a ratio of the sum of the weight fractions of the additive elements to the sum of the weight fractions of the main constituent elements of the magnetic particles is 1.7 wt % or more.

2. The honeycomb structure according to claim 1, The honeycomb structure, wherein the main constituent elements of the magnetic particles are Fe and Cr.

3. The honeycomb structure according to claim 1, A honeycomb structure, in which the compound containing the additional element is present on the surface of the magnetic particles in the coating layer.

4. A honeycomb structure according to any one of claims 1 to 3, A honeycomb structure, wherein the coating layer has a relative density of 75 to 95%.

5. A honeycomb structure according to any one of claims 1 to 3, The honeycomb structure has a coating layer having a thickness of 20 to 100 μm.

6. A honeycomb structure according to any one of claims 1 to 3, A honeycomb structure, wherein the maximum width of a gap between the surface of the target cell and the coating layer is 15 μm or less.

7. A honeycomb structure according to any one of claims 1 to 3, The coating layer is a thick portion where the thickness is locally maximum; a thin-walled portion where the thickness is locally minimized; having A honeycomb structure, wherein the ratio of the thickness of the thick portion to the thickness of the thin portion is 2 or less.

8. A method for manufacturing a honeycomb structure, comprising: a) preparing a substrate, the substrate being a tubular member and having a plurality of cells extending from one end surface to the other end surface; b) preparing a slurry containing magnetic particles and a clay mineral; c) applying the slurry to a surface of a target cell that is at least a portion of the plurality of cells; d) drying and baking the slurry applied to the target cell to form a coating layer on the surface of the target cell; A method for manufacturing a honeycomb structure comprising the steps of:

9. A method for manufacturing a honeycomb structure according to claim 8, A method for manufacturing a honeycomb structure, wherein the clay mineral comprises at least one selected from the group consisting of montmorillonite, sepiolite, hectorite, halloysite and attapulgite.

Citation Information

Patent Citations

  • Catalyst carrier and method for producing same, and exhaust gas purification device

    JP2019188272A